Modeling climate change impacts on the potential distribution of bighorn sheep in Mexico - Zamora-Maldonado, Hilda C.; Avila-Foucat, V. Sophie; Sánchez-Sotomayor, Víctor G. (Frontiers in Climate, 2025)
Climate change is expected to significantly reshape the geographic distribution of many species worldwide. The bighorn sheep (Ovis canadensis), a species of ecological, economic, and cultural importance in Mexico, is particularly vulnerable to these environmental shifts. This study applies ecological niche modeling to estimate the probability of species occurrence based on bioclimatic variables under future climate scenarios. Using four Representative Concentration Pathways (RCP 2.6, 4.5, 6.0, 8.5) and six General Circulation Models, projections are made for the period 2041–2060. This analysis is based on 280 georeferenced records of bighorn sheep occurrences and evaluates changes in temperature and precipitation, which are assumed to influence their potential distribution. Projections suggest a significant reduction in geographic distribution, with drier periods and extreme temperatures exerting the most detrimental effects. These findings pose considerable challenges for long-term conservation and management of bighorn sheep populations, as current strategies may be insufficient. The ecological niche model suggests focusing conservation efforts on Northern Baja California (Californian ecoregion) to identify potential distribution. This research emphasizes the critical need to integrate climate projections into conservation strategies to better manage the uncertainties of climate change.